2011
DOI: 10.1093/cercor/bhr127
|View full text |Cite
|
Sign up to set email alerts
|

Differential Contribution of Right and Left Parietal Cortex to the Control of Spatial Attention: A Simultaneous EEG-rTMS Study

Abstract: We have recently shown that interference with repetitive transcranial magnetic stimulation (rTMS) of right posterior intraparietal sulcus (IPS) cortex during the allocation of spatial attention leads to abnormal desynchronization of anticipatory (pretarget) electroencephalographic alpha rhythms (8-12 Hz) in occipital-parietal cortex and the detection of subsequently presented visual targets (Capotosto et al. 2009). Since lesion data suggest that lesions of the right frontoparietal cortices produce more severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 70 publications
10
57
1
1
Order By: Relevance
“…Moreover, since several previous findings showed a behavioral impairment after IPS stimulation during attention tasks (Capotosto et al, 2009) (Capotosto et al, 2012a) , it is unlike that the present null result for IPS is due to its resiliency to TMS. Furthermore, it can be speculated that the TMS effects on the targeted visual areas should be extended only within the visual network since it exhibits high local efficiency (i.e.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Moreover, since several previous findings showed a behavioral impairment after IPS stimulation during attention tasks (Capotosto et al, 2009) (Capotosto et al, 2012a) , it is unlike that the present null result for IPS is due to its resiliency to TMS. Furthermore, it can be speculated that the TMS effects on the targeted visual areas should be extended only within the visual network since it exhibits high local efficiency (i.e.…”
Section: Discussioncontrasting
confidence: 96%
“…The parameters are consistent with published safety guidelines for TMS stimulation (Rossi et al, 2009). Of note, previous studies have shown that such stimulation has effect for at least 2 sec, thus affecting target processing (Capotosto et al, 2009) (Capotosto et al, 2012a) (Capotosto et al, 2012b).…”
Section: Procedures For Rtms and Identification Of Target Scalp Regionsmentioning
confidence: 95%
“…As these studies have been reviewed recently (Taylor and Thut, 2012), we will not go into great detail here but will briefly mention the main findings. Most importantly, TMS over both frontal and parietal nodes of the dorsal network has an effect on the EEG responses in the context of attention tasks (Capotosto et al, 2009(Capotosto et al, , 2011(Capotosto et al, , 2012Sauseng et al, 2011;Taylor et al, 2007). Moreover, the typical changes in posterior alpha power that can be observed when attention is shifted towards one hemifield are often attenuated with TMS along with corresponding behavioral changes.…”
Section: Multimodal Approaches With Tmsmentioning
confidence: 99%
“…Hemodynamic activity in the Dorsal Attention Network (DAN; Corbetta and Shulman, 2002) is negatively correlated with electroencephalographic (EEG) alpha power (Laufs et al, 2003; Shadaghiani et al, 2010), whereas regions of the default mode network (DMN; Mo et al, 2012; Ben-Simon et al, 2008) and cingulo-opercular network (CON; Dosenbach et al, 2007; Laufs et al, 2003; Shadaghiani et al, 2010, 2012) have shown the opposite relationship. Correspondingly, repetitive transcranial magnetic stimulation (rTMS) of DAN's right inferior parietal sulcus (IPS) or right frontal eye fields (FEF) suppresses both posterior alpha desynchronization and the detection advantages normally accompanying shifts of spatial attention (Capotosto et al, 2012; Hamidi et al, 2009). …”
Section: Introductionmentioning
confidence: 99%